PENGARUH MINAT BELAJAR, DUKUNGAN ORANG TUA DAN LINGKUNGAN BELAJAR TERHADAP PERILAKU BELAJAR SISWA DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA (Studi Faktor Yang Mempengaruhi Prilaku Belajar dan Hasil Belajar Siswa Kelas 4,5 dan 6 Pada SDN Binuang 4 da - Mahdalena Mahdalena (JURNAL KINDAI, 2022)
The writing of this idea departs from a theoretical framework, experts, or understanding of various experiences, then developed into problems - problems solving - solutions proposed to obtain justification (verification) in the form of empirical data support. This study aims to determine how much influence learning interest, parental support and learning environment have on student learning behavior and student learning outcomes in science subjects (study of factors influencing learning behavior and student learning outcomes in grades 4,5 and 6 at SDN Binuang 4 and SDN Binuang 8 in Binuang District, Tapin Regency in Science Lessons), The method used in this study is a quantitative method, with a population of 156, a sample of 156 people and data analysis techniques with research instruments validity testing, reliability testing, and using path analysis. path analysis.The results of this study indicate that (1) interest in learning has a significant effect on the learning behavior of students at SDN Binuang 4 Tapin Regency and SDN Binuang 8, Tapin Regency, Binuang Regency, Tapin Regency in science lessons (2) Parental Support has a significant effect on Student Learning Behavior at SDN Binuang 4 Regency Tapin and SDN Binuang 8 Tapin District, Binuang District Tapin District in science lessons (3) The learning environment has a significant effect on student learning behavior at SDN Binuang 4 Tapin Regency and SDN Binuang 8 Tapin District Binuang District Tapin Regency in science lessons (4) Interest in learning has a significant effect on Student Learning Outcomes at SDN Binuang 4 Tapin District and SDN Binuang 8 Tapin District Binuang District Tapin District in science lessons (5) Parental support has a significant effect on student learning outcomes at SDN Binuang 4 Tapin District and SDN Binuang 8 Tapin District Binuang District Tapin Regency in lesson a ku PA (6) Learning Environment has a significant effect on Student Learning Outcomes at SDN Binuang 4 Tapin Regency and SDN Binuang 8 Tapin District Binuang District Tapin Regency in science lessons (7) Learning Behavior has a significant effect on Student Learning Outcomes at SDN Binuang 4 Tapin Regency and SDN Binuang 8 Tapin District, Binuang District, Tapin District in science lessons